Types of mesoplastic waste in the Manggar Beach tourism area, Balikpapan City, East Kalimantan - Rifanka, Muhammad Akbar; Ritonga, Irwan Ramadhan; Eryati, Ristiana (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2025)
Plastic waste poses a significant threat to the global environment, particularly in coastal and marine ecosystems. Among its various forms, mesoplastics, measuring between 5 and 25 mm have attracted considerable attention. This study aims to identify and analyze the types, weights, quantities, compositions, and densities of mesoplastics found along Manggar Beach, a tourist destination in Balikpapan City, East Kalimantan. Sampling was conducted in two periods: April (Period I) and August (Period II) of 2022. A purposive sampling method was applied using a 100-meter transect line divided into 5x5 meter lanes, followed by the placement of 1x1 meter quadrats. In Period I, four types of mesoplastics were identified as film, fiber, fragments, and styrofoam, while only film was detected in Period II. A total of 43 mesoplastic particles (weighing 9.45 grams) were recorded in Period I, compared to just 5 particles (0.15 grams) in Period II. By weight, styrofoam made up the largest proportion (49%) in Period I, whereas film accounted for 100% in Period II. The average mesoplastic density observed in this study was 0.38 particles per square meter.